2016
DOI: 10.1080/2162402x.2016.1175794
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-derived IL-1α induces CCL22 and the recruitment of regulatory T cells

Abstract: In cancer patients, immunosuppression through regulatory T cells (Treg) is a crucial component of tumor immune evasion and contributes to disease progression. Tumor-infiltrating Treg in particular suppress local effector T cell responses and are associated with poor prognosis in tumors such as human pancreatic cancer or hepatocellular carcinoma (HCC). The chemokine CCL22 is known to recruit Treg into the tumor tissue and many types of human tumors are known to express high levels of CCL22. The mechanisms leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 49 publications
2
57
0
1
Order By: Relevance
“…While the most effective immunotherapies in development seek to generate, promote, or stimulate tumorspecific CTLs, tumors often induce an immunosuppressive microenvironment that allows them to evade immune cell killing [4]. A major mechanism of tumorinduced immunosuppression is the recruitment and/or induction of CD4+ regulatory T cells (T REGS ) within the tumor microenvironment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…While the most effective immunotherapies in development seek to generate, promote, or stimulate tumorspecific CTLs, tumors often induce an immunosuppressive microenvironment that allows them to evade immune cell killing [4]. A major mechanism of tumorinduced immunosuppression is the recruitment and/or induction of CD4+ regulatory T cells (T REGS ) within the tumor microenvironment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…46 The recruitment of Tregs in HCC occurs via the CCR6-CCL20 axis 47 and CCL22 induction by tumor cell-secreted IL-1α. 48 FoxP3 is not only essential for development of Tregs but also remains the best marker to identify these cells. However, several studies have shown that activation of human non-Tregs can also lead to expression of FoxP3 in vitro , suggesting that this marker needs to be used with caution.…”
Section: Regulatory T-cellsmentioning
confidence: 99%
“…DC maturation and activation is also hindered by confrontation with immunosuppressive cytokines TGFß, IL6, IL10, and GM-CSF, which activate the STAT3 pathway (693)(694)(695). Furthermore, costimulatory molecule CD40 and CD80 expression is reduced in DC, hampering T-cell activation (696). Instead, DC produce CCL22, which recruits Treg (697, 698).…”
Section: Dendritic Cellsmentioning
confidence: 99%